Regenerasi Tanaman pada Kultur Antera Padi: Pengaruh Persilangan dan Aplikasi Putresin - Iswari S. Dewi; Bambang S. Purwoko; Hajrial Aswidinnoor; Ida H. Somantri (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
The efficient use of anther culture in crop improvement depends on the success of plant regeneration techniques and the recovery of sufficient number of either green haploid plants that may be artificially or spontaneously doubled yielding homozygous diploid pure lines in first generation.  Putrescine, one of growth regulator polyamines, was known as essential factor in embryogenesis on various plant tissues.  The objective of this research was to study the effect of crosses and putrescine application on certain stages of culture most efficient in increasing green plant regeneration.  The experiment was arranged factorially. The first factor was reciprocal crosses of Taipei 309 to Asemandi and Asemandi to Taipei 309.  The second factor was application of putrescine consisted of control (M0: N6 induction medium and MS regeneration medium); M1: N6 induction medium,  MS regeneration medium + 10-3 M putrescine;  M2: N6 induction medium + 10-3 M putrescine, MS regeneration medium;  and M3: N6 induction medium + 10-3 M putrescine, MS regeneration medium + 10-3 M putrescine.  The results indicated that the addition of 10-3 M putrescine into callus induction and plant regeneration media was the best in increasing number and percentage of responding anther, callus formation, responding calli, green plants and number of total plants.  Rice anther culture efficiency, which was indicated by ratio of green plant to responding calli and percentage of green plant to number of anther innoculated, was also increased by the addition of 10-3 M putrescine. At that best treatment maternal effect showed in number of calli producing green plantlets, number of green plantlets, and percentage of green plant to number of anther innoculated. F1 from Taipei309/Asemandi was better  than F1 from Asemandi/Taipei30.   Key words :  Rice, anther culture, putrescine, green plant, reciprocal crosses